Salicylic Acid‐Catalyzed One‐Pot Hydrodeamination of Aromatic Amines by tert‐Butyl Nitrite in Tetrahydrofuran. Issue 16 (19th June 2017) - Felipe‐Blanco, Diego; Alonso, Francisco; Gonzalez‐Gomez, Jose C.
Abstract: A significant acceleration in the hydrodeamination of in situ formed diazonium salts (from aromatic amines) has been observed in the presence of 10‐mol% salicylic acid, using tetrahydrofuran as the hydrogen donor. The reaction proceeds efficiently at 20 °C for a wide range of substituted anilines, even at 10‐mmol scale, without any other additive. The same protocol has been adapted to the selective deuterodeamination of some aromatic amines. Control experiments clearly show that aryl radicals are involved in the reaction mechanism. Abstract :